Statistics for the Behavioral Sciences - Gravetter, Frederick J. and Wallnau, Larry B. (Andover Cengage Learning, 2013)
Statistics for the Behavioral Sciences + SPSS for the Health and Behavioural Sciences +
Include Index
Keywords: Psychology--Statistical methods -- Educational statistics -- Social sciences--Statistical methods